Carbon nanofiber type and content dependence of the physical properties of carbon nanofiber reinforced polypropylene composites. Issue 1 (26th March 2013) - Paleo, A.J.; Sencadas, V.; van, F.W.J.; Lanceros‐Méndez, S.; Ares, A.
<x xml:space="preserve">Abstract</x> The variation of the physical properties of four different carbon nanofibers (CNFs), based‐polymer nanocomposites incorporated in the same polypropylene (PP) matrix by twin‐screw extrusion process was investigated. Nanocomposites fabricated with CNFs with highly graphitic outer layer revealed electrical isolation‐to‐conducting behaviors as function of CNF's content. Nanocomposites fabricated with CNFs with an outer layer consisting on a disordered pyrolitically stripped layer, in contrast, revealed better mechanical performance and enhanced thermal stability. Further, CNF's incorporation into the polymer increased the thermal stability and the degree of crystallinity of the polymer, independently on the filler content and type. In addition, dispersion of the CNFs' clusters in PP was analyzed by transmitted light optical microscopy, and grayscale analysis (GSA). The results showed a correlation between the filler concentration and the variance, a parameter which measures quantitatively the dispersion, for all composites. This method indicated a value of 1.4 vol% above which large clusters of CNFs cannot be dispersed effectively and as a consequence only slight changes in mechanical performance are observed. Finally, this study establishes that for tailoring the physical properties of CNF based‐polymer nanocomposites, both adequate CNFs structure and content have to be chosen. POLYM. ENG. SCI., 54:117–128, 2014. © 2013 Society of Plastics Engineers